2020
DOI: 10.1002/ab.21877
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the menstrual cycle on reactive and proactive aggression in borderline personality disorder

Abstract: Borderline personality disorder (BPD) is characterized by rapidly shifting symptoms, including intense anger and aggressive behavior. Understanding how fluctuations in ovarian hormones across the menstrual cycle may contribute to symptom instability is key for accurate assessment of BPD symptoms and effective interventions. Reactive and proactive aggression, as well as anger in and out, were assessed daily in 15 physically healthy, unmedicated naturally cycling female individuals without dysmenorrhea meeting c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“… 167 In this same sample, anger/irritability was highest in the perimenstrual phase, with reactive aggression highest in the mid-luteal phase and proactive aggression highest during ovulation and lowest perimenstrually. 168 …”
Section: Resultsmentioning
confidence: 99%
“… 167 In this same sample, anger/irritability was highest in the perimenstrual phase, with reactive aggression highest in the mid-luteal phase and proactive aggression highest during ovulation and lowest perimenstrually. 168 …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, two studies revealed a link between cyclical menstrual changes and BPD-like features in non-clinical samples ( 6 , 21 ). Two studies demonstrated menstrual cycle-related changes in BPD symptoms in unmedicated women with regular menstrual cycles in clinical samples ( 24 , 54 ). Considering these four studies, it appears that individuals with BPD had a clear pattern of perimenstrual (i.e., late luteal phase to day 3 of menses) exacerbation, with symptoms of irritability and anger appearing in the luteal phase and peaking in the perimenstrual phase.…”
Section: Bpd Symptoms Across the Menstrual Cyclementioning
confidence: 99%
“…One study to date has evaluated the relationship of PA and female sex-specific hormones ( Table 2 ). Peters and coauthors [ 74 ] quantified PA and the ovulatory hormones estradiol and progesterone in a small sample ( n = 15) of naturally cycling women with BPD. PA, measured using the RPQ, was highest during the follicular and ovulatory cycle phases, where progesterone was lowest.…”
Section: Hormonesmentioning
confidence: 99%